Formação de educadores populares : análise da experiência educativa de creches comunitárias vinculadas a Associação de Educadores Populares de Porto Alegre AEPPA - Oliveira, Graciete Maria de (2008)
This dissertation aims at researching the formation of popular educators. Adopting a qualitative perspective and case study method, this investigation was carried out through the investigation into the practice of popular educators from daycare center linked to AEPPA (Popular Educators Association from Porto Alegre),contextualizing the historical development of daycare centers, analyzing the formation and the practice of the educators from this institution (AEPPA), and checking the relationship between teology and educational contexts "Teo-Pedagógica" contribution. Its central focus is the reflection on life experience knowledge and its reconstructed knowledge concerning the practice of popular educators after continuing education proposed by AEPPA. The text is structured into three chapters. In the first chapter, the research has shown that the Teo-pedagogia provides enough evidences to establish a liberating education proposal. In the second chapter, the methodological process is developed explaining all the elements of qualitative perspective proposal that has been implemented. Finally, the third chapter is an analysis of the data collected based on theoretical aspects, highlighting the most significant features related to the main problem of this dissertation.The conclusions of this research indicate that there is a history to be rescued and analyzed as well as proposals to be concluded. Through pupils, the insertion of educators in a daycare center has shown the possibility of redemption of their place as citizens. This possibility is coming true at AEPPA and its collective commitment to the construction of a liberating education that goes beyond the epistemological dimension, articulating to the political and aesthetic dimensions. This is a new feasible way of democratically, resignified the functions of the popular educator in order to maximize its contribution to the Teo-pedagogical democratic management working in daycare centers.